2019
DOI: 10.4067/s0718-18762019000200110
|View full text |Cite
|
Sign up to set email alerts
|

Whether to Delay the Release of eBooks or Not? An Analysis of Optimal Publishing Strategies for Book Publishers

Abstract: The eBooks market has been growing rapidly in recent years. At the same time, evidence shows that eBooks are cannibalizing the market for physical books. To alleviate the cannibalization effect between eBooks and physical books, publishers may choose to delay the release of eBooks or physical books for a period of time. Adopting a stylized two-period model, this paper investigates three publishing strategies for a monopolistic publisher: delaying the release of eBooks, delaying the release of physical books, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In a natural experiment conducted by Chen et al. (2019), when e‐books are popular in past years, delaying e‐books only hurts the sales volumes of e‐books but leads no increase in p‐books. Thus, when consumers prefer e‐books, the simultaneous is more profitable.…”
Section: Results and Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a natural experiment conducted by Chen et al. (2019), when e‐books are popular in past years, delaying e‐books only hurts the sales volumes of e‐books but leads no increase in p‐books. Thus, when consumers prefer e‐books, the simultaneous is more profitable.…”
Section: Results and Insightsmentioning
confidence: 99%
“…Li et al. (2019a) claim that the publisher should delay the format with less market potential. Early studies have shown that when inventory is short, consumers may turn to different variants of the same brand (Emmelhainz et al., 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Hua, et al [3] first investigate the impact of e-books on the publishers' distribution channel choices. Li, et al [21] and Li, et al [22] examine the publisher's pricing and launch strategies and discover the publisher's publishing sequence is related to the market potential. Chen and Tang [23] formulate a model to analyze the selfpublishing model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They examined the impacts of online-offline channel integration on purchase decisions and found that the integrated dual-channel approach can improve competitive advantage. Li et al [8] studied one monopolistic publisher with both physical and electronic channels. They found that by coordinating the sale times and prices for the different channels, the profits of publishers could be effectively enhanced.…”
Section: Literature Reviewmentioning
confidence: 99%